The Selection of a Process Management Software with Fuzzy Topsis Multiple Criteria Decision Making Method - Şen, Arda Yiğit; Semiz, Neslihan; Algül, Duygu; Güneş, Buse; Demirok Dönmez, Nurcan; Gergin, Zeynep (Springer, 2018)
Today’s retail companies are facing with many different criteria in choosing the software they use to manage their processes. The choice of appropriate software is a multi-criteria decision-making problem that requires process managers to come together with multiple factors as well as with different decision makers. In this study, the problem of choosing process management software for a retailer operating in the textile sector is discussed. The main problem in existing software used in the company’s process management department is that it does not cover all process flows causing lack of commu- nication with other softwares. With this study, it is aimed to reduce time loss in operations by selecting a software that combines processes in one system. Thus, in all departments, there will be a unified and single reporting system for real- time analysis of statistics and better cooperation. In this study, the Analytic Hierarchy Process (AHP) and Fuzzy TOPSIS approaches are presented for this multi criteria decision making problem. In the first step, the AHP implementation and the pairwise comparisons taken from the seven decision makers determined the importance weights of the integrated decision criteria. In the second step, the Fuzzy TOPSIS method is carried out for the selection of the best software with the quantitative and qualitative evaluations of the decision makers.
Keywords: Multi-criteria decision making; AHP; Fuzzy TOPSIS